Analisis Karakter Tanggung Jawab Pada Siswa Kelas V di MI Hidayatussibyan NW Sengkerang - Hanapi, Hanapi; Septina, Herliana Sri; Anwar, Khairil (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is a qualitative research through a descriptive approach. The  purpose of this study was to determine the character of responsibility in grade V students. The subjects of this study were students in grades V at MI Hidayatussibyan NW Sengkerang,  even semester, 2023/2024 academic year. Based on the results of the analysis, it shows that  the character of responsibility possessed by grade V students at MI Hidayatussibyan NW  Sengkerang includes carrying out tasks that are well received and full of readiness,  completing things responsibly, doing tasks according to their abilities, thinking before acting and considering the consequences. exists, is responsible for attitudes, words and actions and  is responsible for attitudes, words and actions. This happens because of habituation to be able to shape the character of student responsibility which is carried out in school.